Fatigue strength of welded structures - Maddox, S. J. (Stephen John) 1944- (Abington Pub., 2002)
The key to avoidance of fatigue, which is the main cause of service failures, is good design. In the case of welded joints, which are particularly susceptible to fatigue, design rules are available. However, their effective use requires a good understanding of fatigue and an appreciation of problems concerned with their practical application. Fatigue strength of welded structures has incorporates up-to-date design rules with high academic standards whilst still achieving a practical approach to the subject. The book presents design recommendations which are based largely on those contained in recent British standards and explains how they are applied in practice. Attention is also focused on the relevant aspects of fatigue in welded joints which are not yet incorporated in codes thus providing a comprehensive aid for engineers concerned with the design or assessment of welded components or structures. Background information is given on the fatigue lives of welded joints which will enable the engineer or student to appreciate why there is such a contrast between welded and unwelded parts, why some welded joints perform better than others and how joints can be selected to optimise fatigue performance.